Video Data Hiding for Managing Privacy Information in Surveillance Systems. (15th October 2009) - Paruchuri, Jithendra K.; Cheung, Sen-ching S.; Hail, Michael W.
Abstract : From copyright protection to error concealment, video data hiding has found usage in a great number of applications. In this work, we introduce the detailed framework of using data hiding for privacy information preservation in a video surveillance environment. To protect the privacy of individuals in a surveillance video, the images of selected individuals need to be erased, blurred, or re-rendered. Such video modifications, however, destroy the authenticity of the surveillance video. We propose a new rate-distortion-based compression-domain video data hiding algorithm for the purpose of storing that privacy information. Using this algorithm, we can safeguard the original video as we can reverse the modification process if proper authorization can be established. The proposed data hiding algorithm embeds the privacy information in optimal locations that minimize the perceptual distortion and bandwidth expansion due to the embedding of privacy data in the compressed domain. Both reversible and irreversible embedding techniques are considered within the proposed framework and extensive experiments are performed to demonstrate the effectiveness of the techniques.